Professional Communication in the Pedagogical Activity of a Teacher - Ibrokhimovich, Soliyev Rakhimjon; Yusupovich, Ibragimov Vakhobjon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article considers the importance of speech and professional communication in the pedagogical activity of a University teacher.